2013
DOI: 10.1371/journal.pone.0069035
|View full text |Cite
|
Sign up to set email alerts
|

Socio-Economic Burden of Influenza among Children Younger than 5 Years in the Outpatient Setting in Suzhou, China

Abstract: BackgroundThe disease burden of children with laboratory-confirmed influenza in China has not been well described. The aim of this study was to understand the epidemiology and socio-economic burden of influenza in children younger than 5 years in outpatient and emergency department settings.MethodsA prospective study of laboratory-confirmed influenza among children presenting to the outpatient settings in Soochow University Affiliated Children's Hospital with symptoms of influenza-like illness (ILI) was perfor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
28
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 21 publications
(31 citation statements)
references
References 33 publications
2
28
1
Order By: Relevance
“…Suzhou is the most economically developed city in Jiangsu province with a resident population of 10,460,000 of which 960,000 are children less than 14 years of age, per the 2010 Census. An investigation of medical records showed that in 2011 the total number of outpatient visits among children less than 5 years of age at this hospital was 396,568, which accounted for approximately 28.5% of all outpatient visits among children this age in the municipal district of Suzhou [16]. A health care utilization survey conducted in 2012 showed that among the municipal districts of Suzhou, 65.2% of children less than 5 years old requiring hospitalization were admitted at SCH (data unpublished).…”
Section: Study Sitementioning
confidence: 99%
See 2 more Smart Citations
“…Suzhou is the most economically developed city in Jiangsu province with a resident population of 10,460,000 of which 960,000 are children less than 14 years of age, per the 2010 Census. An investigation of medical records showed that in 2011 the total number of outpatient visits among children less than 5 years of age at this hospital was 396,568, which accounted for approximately 28.5% of all outpatient visits among children this age in the municipal district of Suzhou [16]. A health care utilization survey conducted in 2012 showed that among the municipal districts of Suzhou, 65.2% of children less than 5 years old requiring hospitalization were admitted at SCH (data unpublished).…”
Section: Study Sitementioning
confidence: 99%
“…Specimens were stored at −20 • C and sent to Suzhou CDC laboratory, one of the national ILI network laboratories, every 2 days to test for influenza by rRT-PCR [16].…”
Section: Data Collectionmentioning
confidence: 99%
See 1 more Smart Citation
“…3 Furthermore, the influenza virus is also implicated in a large number of outpatient visits and subsequent hospitalization, accounting for 10%-26% of outpatient visits with influenza-like illness (ILI) and 6%-14% pneumonia hospitalization in East and South-East Asia. [4][5][6][7] Children, older persons, individuals with chronic respiratory diseases and the immunocompromised are considered high-risk groups for complications from influenza viral infections. 5 Clinical manifestations have also been known to differ with age, as older adults are less likely to report classical ILI symptoms.…”
Section: Introductionmentioning
confidence: 99%
“…69 In Chinese children aged <5 y, 41% of children infected by influenza need to see a doctor more than twice on average. 70 In China, a series of studies on etiology of acute respiratory infection showed that the positive rate for influenza in ILI or ARI cases is 3.2% to 25.8% in outpatient and emergent children respectively, 70-75 and 1.4%-35.4% in inpatient children. [76][77][78][79][80][81] The risk of death in children with underlying diseases is significantly higher than healthy children.…”
Section: Childrenmentioning
confidence: 99%